Have a plate full of chemical-free vegetables - Rai, A B; Saha, Sujoy (Indian Horticulture, 2015)
Knowingly or unknowingly farmers keep applying banned or restricted chemicals for pest and disease management. It is extremely important to replace the usage of extremely and highly toxic chemicals with those having safer mammalian and environmental toxicity profiles. Food safety is not only an issue to promote export of fruits and vegetables, but it applies for the safety of domestic consumers as well. It is essential to initiate bioefficacy and residue dynamic studies on new generation agrochemicals so that food safety to consumers can be ensured in appropriate perspectives. In this endeavour, pro-active, collaborative and supportive participations of agrochemical industries, government bodies and academic institutions are essential.